Between Mundane and Sensational: the “Crisis” of Museums in Age of Mass Consumption (Itinera, 2016)
The essay focuses on the idea of crisis in museums, analyzed through Jean Clair’s work Malaise dans les musées. Starting from the Centre Pompidou, in the age of mass consumption the museum is no longer a place devoted to study and education, but it has become an amusement location and a mass tourist attraction. Mostly thanks to its seductive and appealing architectural structure, the museum itself is now a work of art and the Guggenheim Foundation perfectly embodies the role of museum during the archistar’s era.